Bidding behaviour in interdependent markets for electricity and green certificates - Ganhammar, Kajsa (Energy Economics, 2025)
Market-based climate policies have received increased attention, making it important to understand how they affect competition in the electricity market. This paper focuses on the green certificate policy which financially supports producers of renewably sourced electricity by means of tradable certificates, and develops a duopoly model that incorporates both the electricity and the green certificate markets in an auction-based setting. Producers are privately informed about their generation costs, and the results suggest that whether or not they are drawn from the same distribution has important implications for market outcomes. In particular, if the subsidised technology has a higher expected marginal cost than the conventional one (e.g., one bio-fuelled and one fossil-fuelled technology), the certificate policy can improve competition and efficiency in the electricity market. Conversely, if producers have the same expected marginal cost (e.g., one mature, non-subsidised and one emerging renewable technology), the advantage the policy creates enables the subsidised producer to bid higher at given cost as the probability of winning the electricity auction increases. This undermines competition and results in high consumer prices of electricity.
Keywords: Asymmetric procurement auctions; Electricity markets; Green certificates; Renewable energy